(untitled) (REMUNOM, 2025)
Family and school are the social groups with which children create emotional bonds and develop socially. At school, children will have teachers as allies, who, by creating a stimulating, affectionate and welcoming environment, will allow children to express their ideas, feelings and emotions. The general objective of the research was to investigate the impact of a positive affective pedagogical practice on the learning of third-grade elementary school students. This is a qualitative, descriptive pedagogical intervention research with regard to objectives, carried out with a class of 23 children in the third grade of the Initial Years of Elementary School, 13 boys and 10 girls, aged between 8 and 9 years old, from a state elementary school located in a municipality on the western border of the state of Rio Grande do Sul. Participant observation of the class was carried out with the aim of getting to know it better and being known. In the second week, based on the observations made, a project was drawn up with the intended pedagogical interventions (lesson plans) for the following two weeks. The interventions took place in the afternoon shift in May 2023, and the analysis of the activities carried out and other observations were recorded in a field diary. Photos and videos were also taken in order to document as much as possible the class’s reaction to the interventions. The results showed that children learn and develop through interaction with the environment, with the teacher and with their classmates. The teacher is affectionate when she listens attentively to the child, following their learning process and thinking of different ways to propose pedagogical interventions, helping the child in their formative journey. A positive affective environment is the result of respectful interactions, attentive and sensitive listening, and planned activities.